STRUCTURE AND MAGNETOOPTICAL PROPERTIES OF FINE-GRAIN GARNET THIN-FILMS - ZHANG, HW; KIM, HJ; YANG, SQ (ELSEVIER SCIENCE BV, 1995)
The structure and magneto-optical properties of fine-grain garnet thin films crystallized by the rapid recurrent thermal annealing (RRTA) method have been studied. The RRAT method has been used to crystallize BiGaDyIG garnet single-layer or BiGaDyIG/Al double-layer films and to get nanometer grain size (about 30-50 nm), which results in a large Faraday rotation angle, a smoother surface and fewer voids in the films. Meanwhile we have discovered that the Faraday rotation angle increases with the number of recurrences during the rapid annealing and quenching. With the more recurrent annealing one can not only get a strong Faraday effect, but it suppresses the appearance of DyFeO3 phase in garnet films, which has been explained very well. By applying the new method, the as-deposited films have been successfully crystallized to the (BiDy)(3)(FeGa)(5)O-12 garnet phase. They exhibited excellent magneto-optical porperties with a coercivity of about 1500 Oe and effective Faraday rotation angle of 1.5 degrees. The composition, magnetic and magneto-optical properties of the crystallized garnet films have been examined.